Pengembangan E-Modul Berbasis Flipbook Maker Untuk Meningkatkan Hasil Belajar Pada Tema 6 Subtema 1 di SDN 104231 Batang Kuis - Elysa Bella Sitopu; Lidia Simanihuruk (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to determine the validity of e-modules based on flipbook maker on the theme 6 subtheme 1 in SDN 104231 Trunk Quiz, and, to find out the effectiveness of e-modules based on flipbook maker on theme 6 subtheme 1 in SDN 104231 Trunk Quiz, to know the practicality of e-modules based on flipbook maker on the theme 6 subtheme 1 in SDN 104231 Trunk Quiz. This research uses a type of research and development with the ADDIE model which includes analysis, design, development, implementation, and evaluation. The population of this study were all students of class IV SDN 104231 Trunk quiz. The subject of this study is IV-B class of 30 students, the object of this research is the development of e-module flipbook maker teaching materials on the theme of 6 subthemes 1 learning 1. The results of this study showed an increase in the learning outcomes of students with the theme 6 subtheme 1 in SDN 104231 Trunk Quiz.